Upaya Message Pada Ibu Postpartum Multipara Dalam Penurunan Keluhan Skala Nyeri (Afterpain) Di Kota Makassar - Asikin, Siti Badria`; Hadijah, Hadijah; Rahmawati, Eka; Kristina, Yunita; Anggraini, Arie; Riswanti, Riswanti; Mildaratu, Mildaratu; Sabriana, Riska; Ernawati, Ernawati; Nurmiati, Nurmiati (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The majority of postpartum mothers experienced a decrease in pain after effleurage massage. Effleurage that is done gently and softly can reduce pain, create a sense of comfort and relax tension. This study aims to determine the efforts of message effleurage to reduce pain in postpartum mothers. This research method is a quasi-experimental study with a pretest posttest design approach, namely by involving a group of subjects. The conclusion is that the pain scale before and after treatment in both Postpartum Mothers has changed from severe and moderate pain to moderate and mild pain. The results of the statistical test concluded that there was an effect of the effleurage massage technique on reducing the pain scale in postpartum mothers. The results showed that there was a decrease in the average pain before and after treatment in Postpartum Mothers.